Prodromal Symptoms of Acute Myocardial Infarction in Women: A Systematic Review of Current Evidence - Vincenza Giordano; Rita Nocerino; Caterina Mercuri; Teresa Rea; Assunta Guillari (Nursing Open)
ABSTRACT Aim To synthezise quantitative current evidence on the prodromal symptoms experienced by women before the onset of acute coronary syndrome (ACS), focusing on the prevalence, nature and clinical implications of these symptoms. Design A systematic review. Methods The review adhered to Synthesis without meta‐analysis guidelines and was registered with the PROSPERO database (ID: CRD42024541840). Systematic searches were conducted in PubMed, CINAHL, APA PsycArticles, APA PsycInfo and EMBASE. Included studies were quantitative, focused on women aged ≥ 18 years with confirmed acute coronary syndrome and reported prodromal symptoms. The Quality Assessment with Diverse Studies and the Cochrane Risk of Bias in non‐randomized studies of Interventions tools were used for critical appraisal. Results Of 2170 identified records, 11 full‐text studies were reviewed. The most frequently reported prodromal symptom was unusual fatigue, followed by sleep disturbances and anxiety. Prodromal symptoms often occurred well before the acute event but were frequently misattributed to non‐cardiac causes. Chest pain, typically associated with acute coronary syndrome, was less commonly reported as a prodromal symptom in women, complicating timely diagnosis and treatment. Conclusions The results highlight the need for increased awareness of these early warning signs among healthcare providers and women themselves. Enhanced recognition and understanding of these symptoms could lead to more timely and accurate diagnosis, ultimately improving outcomes for women at risk of acute myocardial infarction. Implications for the Profession and/or Patient Care To educate both health professionals and patients about the variability and significance of prodromal symptoms in women is essential to improve outcomes. Impact This study is the first to systematically review and synthesize the existing literature on prodromal symptoms of acute coronary syndrome specifically in women. The results show l that women are more likely to experience a broader and more complex range of prodromal symptoms, including fatigue, sleep disturbances and anticipatory anxiety, which often precede the acute event. The insights provided by our review could lead to significant improvements in the early diagnosis and treatment of AMI in women, ultimately reducing morbidity and mortality rates associated with cardiovascular diseases. Reporting Method The review has adhered to relevant EQUATOR guidelines and has followed Synthesis without meta‐analysis guidelines. Patient or Public Contribution No patient or public contribution.